2002
DOI: 10.1046/j.1523-1747.2002.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Loss Promotes Survival Primarily by Activating Integrin-Linked Kinase/Akt Without Phosphoinositide 3-OH Kinase Signaling

Abstract: Keratinocyte gangliosides influence cellular functions, including proliferation, adhesion, migration, and differentiation. The effects of endogenous depletion of membrane gangliosides by gene transfection of a human ganglioside-specific sialidase on cell survival were investigated. Ganglioside depletion promotes survival of the human keratinocyte-derived SCC12 cell line through upregulated phosphorylation of beta1 integrin, and increased phosphorylation and activity of integrin-linked kinase, protein kinase B/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…The proliferative pathway appears to be switched off and the differentiation pathway switched on in keratinocytes that have divided up from the basal layer; both effects mediated by their loss of contact with the basal membrane and consequent loss of interaction between integrins and laminins 5/10/11 (Fujisaki and Hattori, 2002;Pouliot et al, 2002). The loss of integrin/laminin interaction inactivates PI3K and subsequently PKB/Akt, and it is noteworthy that one of the kinases that activate Akt by phosphorylation on ser473 is ILK (Delcommene et al, 1998), and it has also been shown that ILK can phosphorylate ser473 of PKB/ Akt in the absence of PI3K-mediated phosphorylation of thr308 (Sun et al, 2002). In the context of these observations, the finding that E7 proteins may increase the PI3K-independent phosphorylation of PKB/Akt, thereby inhibiting apoptosis during viral DNA amplification in the suprabasal layers of HPV-infected host keratinocytes is consistent with our understanding of the HPV life cycle, given that loss of contact with the basal membrane would tend to switch off host cell DNA synthesis as cells begin their normal differentiation schedule.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferative pathway appears to be switched off and the differentiation pathway switched on in keratinocytes that have divided up from the basal layer; both effects mediated by their loss of contact with the basal membrane and consequent loss of interaction between integrins and laminins 5/10/11 (Fujisaki and Hattori, 2002;Pouliot et al, 2002). The loss of integrin/laminin interaction inactivates PI3K and subsequently PKB/Akt, and it is noteworthy that one of the kinases that activate Akt by phosphorylation on ser473 is ILK (Delcommene et al, 1998), and it has also been shown that ILK can phosphorylate ser473 of PKB/ Akt in the absence of PI3K-mediated phosphorylation of thr308 (Sun et al, 2002). In the context of these observations, the finding that E7 proteins may increase the PI3K-independent phosphorylation of PKB/Akt, thereby inhibiting apoptosis during viral DNA amplification in the suprabasal layers of HPV-infected host keratinocytes is consistent with our understanding of the HPV life cycle, given that loss of contact with the basal membrane would tend to switch off host cell DNA synthesis as cells begin their normal differentiation schedule.…”
Section: Discussionmentioning
confidence: 99%
“…SCC12 cells were stably transfected with human plasma membrane ganglioside-specific sialidase cDNA (GenBank TM accession number AB008185, courtesy of Dr. T. Miyagi, Tokyo, Japan) (32) in a pcDNA3 vector using LipofectAMINE reagent (18,22). Gene and protein expression in the resultant SSIA cells were demonstrated by Northern blot and sialidase activity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Gene and protein expression in the resultant SSIA cells were demonstrated by Northern blot and sialidase activity measurements. Ganglioside depletion was shown by thin layer chromatography (TLC) immunostaining (18,20,22). Four SSIA cell lines (SSIA3, SSIA6, SSIA12, and SSIA25) and 2 mock-transfected pcDNA cell lines were studied.…”
Section: Methodsmentioning
confidence: 99%
“…14 ILK kinase activity is stimulated by growth factors and by attachment of cells to the extracellular matrix, namely to FN, [14][15][16] and is localized to the cytoskeletal fraction. 14 Inhibition of the formation of the IPAP1 complex or of ILK activity in epithelial cells has resulted in decreased cell spreading and motility, 8,14,17 growth suppression 18 and apoptosis, [19][20][21][22] and therefore it has been proposed as a potential target for cancer treatment. 23 Cardiac hypertrophy reproduces some of the molecular features of the neoplastic phenotype in other organs and has been associated with remodeling of the extracellular matrix and increased expression and cytoskeletal association of fibronectin (FN), vitronectin and paxillin.…”
mentioning
confidence: 99%